Uterine didelphys with dicavitary twin gestation: A case report - Alison Laura King; Sarah Pixton; Valeria Lanzarone (Elsevier, 2020)
Uterine didelphys is a rare type of congenital uterine anomaly resulting from incomplete fusion of the paramesonephric ducts during embryogenesis. We report the case of a 27-year-old multiparous woman who presented with ovulation-induced dicavitary dichorionic diamniotic twins in known uterine didelphys. At 29 + 5 weeks of gestation, the patient had preterm prelabour rupture of membranes followed by threatened preterm labour in the right uterus only, which settled with tocolysis. The pregnancy continued for a further 9 days, at which time uterine tightenings returned and the right cervix was fully dilated, resulting in successful vaginal delivery of the first twin, leaving the placenta in situ. The left uterus and cervix remained quiescent for a further 24 h before contractions returned, resulting in emergency caesarean section, with the successful delivery of the second twin. As a rare phenomenon, there is sparse literature on the management of dicavitary twin gestation in uterine didelphys. This case report adds to the evidence for independent functioning of uteri and cervices in cases of uterine didelphys which may enable interval delivery delay in this cohort with known increased risk of preterm birth.